Pola pembiakan -dan out putsapi potong di Daerah Istimewa Yyogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The purpose of this research is to study the breeding policy, in order to calculate the out put of beef cattle from DI Yogyakarta. The natural increase should be found first. This study has been done at 4 kabupatens at DIY in 1988, involving a total number of 465 farmers. From the analysis of the data, it was found that the percentage of the adult cows was 45,02 Â± 9,49% with an average of 5,86 years of age. The birth rate was 53,0 Â± 9,5%, equal than 23,-86% of the total population. The natural increase of one year of age was 21,84%. Since the cows were held in the breeding during 6 years, it can he calculated that the out put of beef cattle was 19,84%. The net replacement rate was 130,66% that means that DIY can produce sloughter cattle.